Trophoblast-Targeted Nanomedicine Modulates Placental sFLT1 for Preeclampsia Treatment - Li, Lei; Yang, Huijun; Chen, Pengzheng; Xin, Tao; Zhou, Qian; Wei, Dan; Zhang, Yanan; Wang, Shan (Frontiers in Bioengineering and Biotechnology, 2020)
The overexpressed soluble fms‐like tyrosine kinase 1 (sFLT‐1) in placenta is considered to be a potential therapeutic target for PE. How to achieve efficient intervention of sFLT1 expression in the placenta is an urgent problem to be solved. PEG-PLA nanoparticle generated by double-emulsion methods is a novel siRNA delivery system. Synthetic placental CSA binding peptide (P-CSA-BP) is effective for targeting lipid-polymer nanoparticle to the placenta. We conjugated P-CSA-BP to the surface of PEG-PLA nanoparticle to create a novel placenta specific sFLT1 siRNA delivery system for the therapy of preeclampsia (PE). Nanoparticles were synthesized using double emulsion method and characterized by dynamic light scattering and transmission electron microscopy. RT-PCR was employed to evaluate mRNA level and protein level was analyzed by ELISA kit. The tissue distribution of nanoparticles was observed through ex vivo images. The concentrations of nanoparticles in organs were measured using high-performance liquid chromatography. T-NPsisFLT1 had higher efficiency than NPsisFLT1 in accumulating in HTR-8/SVneo cells and significantly decreased the expression of sFLT1. Intravenously administered T-NPsisFLT1 specifically accumulated in placentas of mice. sFLT1 mRNA level in placenta and protein level in serum were declined by T-NPsisFLT1. T-NPsisFLT1 shown no obvious toxic effect on both mother and fetus. The utility of T-NPsisFLT1 nanoparticles as a sFLT1 siRNA placenta specific delivery system significantly silenced sFLT1 in mice and is safe for both mother and fetus. This nanoparticle is a novel potential therapeutic strategy for PE.